Pemanfaatan Media Grafis Dalam Pembelajaran Ilmu Faraidh - Khoirul Wildani; Badrus, Badrus (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
Faraidh's mastery is needed to overcome the problem of inheritance, while people rarely learn it because the material is abstract and the monotonous presentation gives the impression that it is difficult to learn. The use of graphic media is an alternative that can clarify abstract ideas so that Faraidh's studies can be understood. The purpose of this study is to describe the learning process, and the feasibility of graphic media by looking at its functions and benefits in the learning process of Faraidh Science class II Ulya at Madrasah Ihya' Ulumuddin Lirboyo Kediri. This research is of the field research type descriptive approach, with observation techniques, interviews, and documentation. Data analysis by reducing, presenting, and verifying data, and tested with Credibility Tests in the form of extended observations, triangulation, negative case analysis, and member checks. The results of the study, namely: (1) The implementation of Faraidh learning by utilizing graphic media, is a form of combination of classical learning (Traditional Classes), with direct teaching strategies (Explicit Instruction) and inquiry learning, namely familiarizing participants learn by investigating problems and finding solutions to improve participants' overall interest and learning outcomes. (2) Faraidh learning results show that the overall ability of students has reached the KKM score (6) which means that the use of graphic media in learning Faraidh Science is fairly feasible and effective.